Effects of carbon to nitrogen ratio and organic loading rate on biogas methane production from anaerobic digestion of food waste - Tanimu, Musa Idris (2014)
This study has been concerned with an investigation of biogas methane generation from the abundant food waste (FW) available in Malaysia by anaerobic digestion (AD) process at mesophilic (35oC) conditions. Methane recovered from FW digestion is a source of renewable energy for heat and electricity generation. The biogas generation was carried out in batch digesters and then in 2 semi-continuous mode digesters. The semi-continuous mode digesters consists of a 1000L pilot scale (PS) digester up-scaled from a 10L laboratory scale (LS) anaerobic digester. The key parameters investigated were the effect of carbon to nitrogen (C/N) ratio and the organic loading rate (OLR) of the FW on the biogas methane production. The FW was fed to the digesters at different OLR of 0.5-5.5 g VS /L d in the semicontinuously fed LS and PS digesters and at OL of 0.5-7.5 g VS /Ld in the batch digester. Using a constant hydraulic retention time (HRT) of 12.5 days, each OLR was investigated during the semi-continuous process. Three C/N ratio values of 17, 26 and 30 were studied at batch scale while two C/N ratio values of 17 and 30 were studied during the semi-continuous AD in the LS and PS. The available FW gathered from restaurants around Taman Sri Serdang was at C/N ratio 17. The C/N ratio 26 and 30 fed were formulated by mixing the available FW with calculated proportions of Fruits, vegetables and meat wastes to increase its C/N ratio value. Performance evaluation parameters for AD process such as the COD removal, VS destruction, volatile fatty acids, alkalinity, ammonia-nitrogen and the biogas methane yield were studied during the 30 days batch and 168 days semi-continuous AD process. The highest methane yield obtained from the batch digestion was 0.557 L/g VS fed at an OLR of 5.5 g VS /Ld during the digestion of FW of C/N=30. This compares with the maximum methane yield of 0.510 L/g VS fed obtained at OLR of 5.5 g VS /Ld in the LS digester during the semi-continuous digestion of FW at C/N=30. The maximum methane yield obtained in the PS digester was 0.392 L/gVS at OLR of 4.5gVS/Ld during the digestion of FW at C/N=30. The methane yield attained in the up-scaled PS digester was about 80% of that obtained in the LS. Results showed that process stability and digester treatment performance during semi-continuous digestion was higher during the digestion of FW at C/N=30 than at C/N=17. Foaming potential tests revealed that foaming was initiated during digestion at OLR of 1.5 g VS/Ld in all the feedstock digested. However, the highest foaming volume of 26% recorded was during the digestion of FW of C/N=17 at OLR of 7.5 g VS/Ld. The feedstock with C/N=30 had the least foaming tendency with foaming volume of 10% at OLR of 7.5 g VS/Ld.